Predictors of Refugee Adjustment: The Importance of Cognitive Skills and Personality - Elisabeth Hahn; David Richter; Jur̈gen Schupp; Mitja D. Back (Collabra: Psychology, 2019)
In light of the recent worldwide migration of refugees, determinants of a more or less successful integration are heavily discussed, but reliable empirical investigations are scarce and have often focused on sociodemographic factors. In the present study, we explore the role of several individual characteristics for refugee adjustment in the areas of (a) institutional, (b) interpersonal and (c) intrapersonal adaptation. In a sample of 4,527 refugees (M = 33.6 years, 38% women), we investigated the effect of sociodemographic characteristics (age, gender, months in Germany, religious affiliation), cognitive factors (cognitive ability, educational history, language skills, integration-course participation), and personality (locus of control, risk appetite, willingness to reciprocity) on adjustment parameters. Both, cognitive skills (especially language skills) and personality, showed incremental validity beyond sociodemographic factors for refugee adjustment comparable across contextual factors. Even with respect to contextual factors such as residency status and living situation, results remained largely stable. The study provides first hints on the importance of personality, thereby providing important implications for understanding integration processes and optimizing interventions on personal, social, and societal levels.
Keywords: 330; refugee adjustment; personality; labor market; integration; migration